Study on Consistency of Salt Iodization in Salt Factories - Jabin, SA (Bangladesh Journal of Scientific and Industrial Research, 2009)
The study was conducted among the salt factories located in four different zones-Narayangonj, Chittagong, Patiya and Khulna, who have SIP'S (Salt lodization Plant) and produce iodized Salts. A law was enacted which made the mixing of iodine at 45 to 50 ppm level mandatory to all the salt factories in Bangladesh. The objectives of the sutdy were to determine the iodine level of salts maintained by those factories situated in those four zones. Total 2352 samples were collected from 121 open and regularly operating salt factories. Analysis of results of salt samples showed that total 1338 (56.89%) salts had inadequate iodine (<45 ppm), 175 (7.44%) salts had adequate iodine (40 to 50 ppm) and 839 (35.67%) salts contained higher amount of iodine (>50 ppm). Factory wise, 12.40% factories found producing salts containing inadequate level of iodine, 4.96% factories found producing excess level of iodine, 47.93% factories found producing sometime high or low level of iodine (not adequate level at all) and 34.71% factories found mixing iodine sometimes adequately and other time mixing either inadequately or excess level of iodine. So not a single factory out of 121 factories in those four zones maintains consistency in mixing iodine in iodized salt.) Key words: Iodine, Iodized salt, Salt, Iodization plant, Salt factory, Consistency DOI: 10.3329/bjsir.v44i2.3677 Bangladesh J. Sci. Ind. Res. 44(2), 225-228, 2009